2006
DOI: 10.1007/s10453-005-9008-5
|View full text |Cite
|
Sign up to set email alerts
|

Chilling and heat requirements for the prediction of the beginning of the pollen season of Alnus glutinosa (L.) Gaertner in Ponferrada (León, Spain)

Abstract: Winter-flowering trees such as the alder (Alnus glutinosa (L.) Gaertner) can survive periods of adverse climatic conditions, entering a period of dormancy in the early fall. The end of dormancy and the start of the pollen season require a period of low temperatures followed by another of warm temperatures. These requirements were studied from 1995 to 2002, in order to develop a model to predict the onset of the alder pollen season in Ponferrada (Spain). Chilling accumulation took place from late October to lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
2
14
0
1
Order By: Relevance
“…Negative values correspond to convergence regions that favour the accumulation of airborne particles Aerobiologia significant (p \ 0.05) and negative. Therefore, the presence of these pollen types in the air was influenced by temperature prior to the flowering period (OctoberNovember), which created the conditions necessary to exit the resting metabolic state and initiate the specialisation and development of floral meristems (flowering) and production of pollen (Frenguelli et al 1991;Cesaraccio et al 2004;Yan et al 2004;González-Parrado et al 2006). Subsequently, increases in the photoperiod in late December and rising temperature produced an increase in the presence and abundance of pollen in the air that coincides with reports from aerobiological studies conducted in Monterrey (Rocha-Estrada et al 2008) and Mexico City, which indicated that the flowering period of Fraxinus, Cupressaceae and Alnus occurred during the cold months of the dry season from December to March (Bronillet-Tarragó 1992;Salazar-Coria 1995;Torres-Valdos 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative values correspond to convergence regions that favour the accumulation of airborne particles Aerobiologia significant (p \ 0.05) and negative. Therefore, the presence of these pollen types in the air was influenced by temperature prior to the flowering period (OctoberNovember), which created the conditions necessary to exit the resting metabolic state and initiate the specialisation and development of floral meristems (flowering) and production of pollen (Frenguelli et al 1991;Cesaraccio et al 2004;Yan et al 2004;González-Parrado et al 2006). Subsequently, increases in the photoperiod in late December and rising temperature produced an increase in the presence and abundance of pollen in the air that coincides with reports from aerobiological studies conducted in Monterrey (Rocha-Estrada et al 2008) and Mexico City, which indicated that the flowering period of Fraxinus, Cupressaceae and Alnus occurred during the cold months of the dry season from December to March (Bronillet-Tarragó 1992;Salazar-Coria 1995;Torres-Valdos 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although samples have been collected using Hirsttype spore traps, accurate comparisons cannot be made because of differences in sampling periods and pollen grain counting methods (González-Macías et al 1993;Bronillet-Tarragó 1992;Bronillet 1996;Rosas et al 1998;González-Lozano et al 1999;Torres-Valdos 2006;Cid-Martínez 2007). However, the results of these studies were consistent with the abundance of airborne pollen, with arboreal pollen grains composing the most diverse and abundant group during the dry season (November-April), which is the period when most the trees flower.…”
mentioning
confidence: 98%
“…Quercus (Garcia-Mozo et al 2006;Rodriguez-Rajo et al 2005), Alnus glutinosa (Gonzalez-2 Parrado et al 2006), Prunus padus and Tilia cordata (Thompson and Clark 2006), olive 3 (Perez-Lopez et al 2008) and nine shrubs and trees in the Mediterranean (Spano et al 1999). 4…”
mentioning
confidence: 99%
“…German oaks enter the generative development when the daily temperature sum above 5°C is very similar to the data presented here, about 250 GDDºC when SPS was defined by the Σ5 method (Chałupka 2006). The drawbacks of the GDDºC method are the frequently disputable dates from which the temperatures should be summed, what temperatures should be summed, and what are the proper threshold temperatures (Rodríguez-Rajo et al 2003;Sánchez-Mesa et al 2005;González-Parrado et al 2006;Schieber 2006;Fuertes-Rodríguez et al 2007). In order to develop the most effective method, all possible combinations of variables should be tested.…”
Section: Discussionmentioning
confidence: 97%
“…On the basis of a 6-year study period, Valencia-Barrera et al (2002) showed that in the period preceding pollination of different taxa it is not the temperature but the water that is a more important factor of forecasting. The presented results of the investigation In aerobiological investigations, forecast models for tree pollen were chiefly based on temperature and precipitation, air humidity, irradiance, and sunshine during the months preceding flowering and in the autumn and winter of the previous year (Fairley and George 1986;Rodríguez-Rajo et al 2003;González-Parrado et al 2006;Fuertes-Rodríguez et al 2007;García-Mozo et al 2007). In Rzeszów, the start of oak pollen seasons were significantly correlated with the minimum temperature of March and a forecast would be possible 2 weeks in advance.…”
Section: Discussionmentioning
confidence: 98%